An Effective Selection of Mobile Robot Model Using Fuzzy Logic Approach. (2015) - Sahu, Jagannath; Choudhury, B.B.; Muni, M.K.; Patra, M.R.
Abstract: Mobile robots have been extensively used by many industries as well as organizations for selection of Robot which must be considered with acceptable attributes. The evaluation and ranking of mobile robots are identified with some of the standard attributes of different mobile robot configurations. This paper introduces some qualitative parameters to find out the best mobile robot alternatives. A step-by-step procedure for evaluation of mobile robot is proposed basing on different parameters. In the fuzzy-based method, the weight of each criterion and the rating of each alternative are described by using different membership functions and linguistic terms. By using three techniques triangular, trapezoidal and Gaussian membership functions, the closeness of robot is determined in accordance to capacity of Robot. This paper compares three techniques and found that the Gaussian membership function is the effective one for closeness measurement as its surface plot shows a good agreement with the output result.